From a Collection of Identities to Collective Identity: Evidence From Mainstream and Minority Adolescents in Bulgaria. (November 2014) - Dimitrova, Radosveta; Chasiotis, Athanasios; Bender, Michael; van de Vijver, Fons J. R.
We studied collective identity and psychological well-being in Bulgarian adolescents (305 mainstreamers, 278 Turkish-Bulgarians, and 183 Muslim-Bulgarians). Turkish-Bulgarian and Muslim-Bulgarian minorities (ethnic Bulgarians converted to Islam during the Ottoman Empire) have been subjected to severe assimilation policies until recently. A multigroup confirmatory analysis showed that ethnic, religious, and familial identities were significantly and positively related to a single underlying factor we labeled collective identity . Bulgarian identity was unrelated to collective identity in the Turkish-Bulgarian group. As expected, mainstream adolescents showed a stronger Bulgarian and weaker religious identity than Turkish-Bulgarian and Muslim-Bulgarian adolescents. In all groups, individuals with a stronger collective identity reported higher levels of well-being. We conclude that the concept of collective identity is useful to link various identity components to well-being of youth from different ethnic groups.